2017
DOI: 10.7166/28-3-1853
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Monitoring of Ti6al4v (Eli) Powder Used in Different Selective Laser Melting Systems

Abstract: The characterisation and monitoring of Ti6Al4V (ELI) feedstock powder is an essential requirement for the full qualification of medical implants and aerospace components produced in selective laser melting systems. Virgin and reused samples of this powder were characterised by determining their physical and chemical properties through techniques complying with international standards. This paper presents the results obtained for Ti6Al4V (ELI) powder of two different particle size distributions received from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…This is in contrast with the agglomerates in recycled 316L SS, in which much smaller spherical or near-spherical powder particles are attached to the larger powder particles with similar morphologies. These can be ascribed to the higher tendency of fine particle sizes with narrow size distribution to agglomerate, compared to those possessing comparatively larger particle sizes and wider size distribution, as is the case for the AlSi10Mg and 316L SS powders in this study, respectively [78,79].…”
Section: Morphology and Distributionmentioning
confidence: 59%
“…This is in contrast with the agglomerates in recycled 316L SS, in which much smaller spherical or near-spherical powder particles are attached to the larger powder particles with similar morphologies. These can be ascribed to the higher tendency of fine particle sizes with narrow size distribution to agglomerate, compared to those possessing comparatively larger particle sizes and wider size distribution, as is the case for the AlSi10Mg and 316L SS powders in this study, respectively [78,79].…”
Section: Morphology and Distributionmentioning
confidence: 59%
“…Oxygen and nitrogen are alpha stabilisers in Ti6Al4V parts and may increase the rate of martensitic transformation [2]. Therefore reduced levels of oxygen and nitrogen content associated with Grade 23, allows for improved ductility and fracture toughness properties desired for biomedical and cryogenic applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Metals 2020, 10, x FOR PEER REVIEW 2 of 14 parts and may increase the rate of martensitic transformation [2]. Therefore reduced levels of oxygen and nitrogen content associated with Grade 23, allows for improved ductility and fracture toughness properties desired for biomedical and cryogenic applications [4]. Components fabricated by L-PBF are manufactured in a layer-on-layer manner, from a predetermined computer-aided design (CAD) model.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray micro computed tomography [15] was used in this study using optimization procedures as described in [16]. Metal powder was acquired from a recent study of powders used in different commercial systems [17], with the two demonstrated here originating from commercial supplier TLS Technik GmbH with large size fraction (LENS powder, 40–100 μm) and the other with small particle size distribution (<40 μm) for a DMLS AM machine. These cover the typical size ranges of powders in use commercially in AM systems.…”
Section: The Methodsmentioning
confidence: 99%